Myeloid-Derived Suppressor Cells Are Regulated by Estradiol and Are a Predictive Marker for IVF Outcome - Hu, Cong; Zhen, Yu; Pang, Bo; Lin, Xiuying; Yi, Huanfa (Frontiers in Endocrinology, 2019)
In vitro fertilization (IVF) is an effective means to treat infertility, but the pregnancy rate is still unsatisfactory, reliable markers to predict pregnancy outcome are ill-defined. Myeloid-derived suppressor cells (MDSC) are critically involved in decisions related to the acceptance or rejection of foreign fetal antigens by the maternal immune system. However, factors that regulate peripheral blood MDSC during pre-pregnancy are poorly defined. Thus, the goal of this study was to assess the relationships among serum estradiol (E2) and endothelial growth factor (VEGF) levels, MDSC ratio, and pregnancy outcome associated with IVF. Patients undergoing IVF treatment (n = 54) were recruited from January to June 2018. Levels of E2 and VEGF were measured by ELISA, MDSC ratios among peripheral blood mononuclear cells (PBMC) were detected by flow cytometry, and the crosstalk among these parameters was analyzed. A receiver operating characteristic curve (ROC) of MDSC levels were plotted to assess this measure as an independent predictive factor for pregnancy. In addition, we analyzed the possible involvement of molecular pathways by bioinformatics. When E2 levels were less than 4000 pg/ml, the MDSC proportion was positively correlated with serum E2 and VEGF levels. However, when E2 levels were greater than 4000 pg/ml, the MDSC ratio was negatively correlated with E2 levels. A ROC curve revealed that the percentage of MDSC had better sensitivity and specificity at a concentration of 8.22% (0.875 and 0.75, respectively; area under the curve = 0.859) to predict pregnancy success, based on multiple logistic regression analysis. Furthermore, we found 12 target genes of E2 and VEGF, and also functional genes related to MDSC, indicating potential protein–protein interactions underlying these associations. In summary, we showed that E2, depending on its concentration, might play a dichotomous role in influencing the MDSC proportion by regulating VEGF. In IVF patients, an increased MDSC ratio among PBMC was highly correlated with elevated pregnancy rates, independent of the effects of E2, which might provide new insight into immune-related miscarriage and IVF failure.